Port-Site Tuberculosis After Laparoscopy - Baqui, MA (Journal of Armed Forces Medical College, Bangladesh, 2012)
In light of the explosive increase in laparoscopic surgery there is concern about the effectiveness of sterilizing laparoscopic instruments by immersion in 2% gluteraldehyde. This article describes 02 (two) cases who presented with biopsy proven granulomatous lesion of tuberculosis at the port site which were of primary origin. DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10398 JAFMC 2011; 7(2): 47-49